MENYELAMI MAKNA TAFSIR DAN TAKWIL SEBAGAI METODOLOGI MEMAHAMI KANDUNGAN AL-QUR'AN - Setiyawan, Said Ali (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
This article aims to explore comprehensively the discussion regarding interpretation and takwil and related matters. Tafsir and takwil as a methodology in understanding the Al-Qur'an must be understood well so as to produce a product of understanding that can be accounted for. This article is a literature review with steps to collect primary and secondary references. Next, they are analyzed and compared proportionally. This article provides an illustration: tafsir is an attempt to explore the unclear meaning of the Qur'an, related to the meaning of the pronunciation and the possibility of the desired meaning, while takwil is related to a series of sentences and exploring the nature of the desired meaning. An important requirement for both is that they must not conflict with religious law.